Análisis doctrinario y jurídico de los accidentes de trabajo y la responsabilidad patronal en el Ecuador - Carpio Torres, Irma Mercita (2016)
The Ministry of labour and employment, through the management and the Labour Inspectorate has several powers of an administrative nature. This provision gives you full power to act, through work inspectors, in protection of people with "worker or employer" status and whose employment relationship is regulated by the provisions of this legal body. Indeed, a Labour Inspector has jurisdiction for matters that violate the harmony contractual in order to protect or safeguard the rights which by virtue of the legal provisions in force, intend to be unknown or violated. Although the Labour Inspector, an official with powers determined by law, is also known as a "Justice of the peace" as its performance has as main function solutions that favour, both employers and workers; provided that these are framed within the applicable legal rules. However the labour code itself circumscribed roles, competencies and procedures relating to the reception and processing of complaints, which are fulfilled. But the same can be effectuated, because there is no coercive measures in the law which punish the employer not assisted during the proceedings that the inspector requires. The theoretical and field of this thesis work allowed me to obtain criteria, with clear and precise, Fundamentals of well-known literature, contributing to objectives-check, and verification of the hypothesis, allowing you to support the proposed changes. The contents of the thesis is an intellectual effort of the applicant in the field of scientific and methodological, that deals with theoretical and empirically, the problem involving the non-appearance of the employers to the call made by labour on labour claims inspectors, which carried out the relevant analyses, which will allow me to reach conclusions, recommendations and the relevant proposal, which presented it to the University community, for analysis.